Restructuring the Sea: profound shifts in the world's most invaded marine ecosystem. Issue 1 (24th August 2012) - Edelist, Dor; Rilov, Gil; Golani, Daniel; Carlton, James T.; Spanier, Ehud
Abstract: Aim: We examine fish invasions in the south‐eastern Mediterranean as a model system for the invasibility of open coasts and provide perspectives through a review of global marine fish invasions. Location: South‐eastern Mediterranean (Levant Sea). Methods: We compare historical (1990–1994) and modern (2008–2011) trawl surveys from the Mediterranean continental shelf and upper slope of Israel to evaluate the relative abundance and biomass of Indo‐Pacific fishes and their impact on diversity and trophic level (TrL). We examine resultant changes in community composition by both univariate and multivariate analyses, and compliment this study with a critical global review of open coast marine fish invasions. Results: A staggering 55 Indo‐Pacific fish species have established permanent populations in the Mediterranean in the last 142 years, more than any other marine ecosystem. This process is accelerating with 13 of 27 new arrivals having established in the 21st century alone. Invasive fish biomass and abundance proportions in the shallow open coast have doubled in just two decades and today the Levantine ecosystem is dominated by non‐native species. This proliferation has resulted in significant declines of some indigenous species, some to near extirpation levels. Main conclusions: Here, we show that non‐estuarine ecosystems are much more susceptible to large‐scale invasion pressures than previously thought. Our results place invasion in the same category with overexploitation, habitat destruction and pollution, processes normally considered as much more critical perturbations to coastal fish communities. We propose that despite these irreversible alterations, invasions have masked overall TrL changes and diversity declines by replacing native fish with invasives of similar ecological position. As species extirpations increase, we anticipate further declines in indigenous biomass, abundance and diversity in the Mediterranean Sea.